Influence of aggregate on the microstructure of geopolymer - Subaer (Curtin University, 2004)
Inorganic geopolymers or simply geopolymers based on silico-aluminate are relatively novel materials with a wide range of potential applications. The mAln purpose of the present study was to experimentally investigate the compositionmicrostructure- property relationship of these new materials. These must be understood in order to optimise the performance of geopolymers. Geopolymers with different chemical compositions (Si:Al and Na:Al atomic ratios) were prepared by thermally assisted alkali-activation of metakaolinite at 70ºC. Metakaolinite was obtAlned by dehydroxylation of kaolinite at 750ºC for 6 hours. Measurements indicated that the compositions of geopolymers influence the microstructural character as well as the physical and mechanical properties of these materials. Geopolymers prepared with an atomic ratio of Si:Al = 1.04 and 1.25 are categorised as sodium-poly(sialate) (Na-PS) geopolymers. These materials were found to be composed of zeolite-A or zeolite-X in conjunction with amorphous geopolymer. These materials are relatively soft, with low density and high apparent porosity, and have low hardness and compressive strength. Geopolymers prepared with an atomic ratio of Si:Al = 1.50, 1.75 and 2.00 are categorised as sodium-poly(sialate-siloxo) (Na-PSS) geopolymers. The structure of these geopolymers is amorphous as observed by X-ray diffraction (XRD) with no evidence of zeolite formation. A broad amorphous hump in the X-ray diffraction patterns suggests that the Na-PSS geopolymers consist of disordered frameworks with short-range order. The thermal analysis of Na-PSS by means of thermogravitmetric-differential thermal analysis (TG-DTA) revealed that about 15% of the initial reaction water remAlns in the geopolymer framework. The DTA curves for Na-PSS show a single endothermic peak around 135ºC due to water evolution.Na-PSS geopolymers exhibit substantial shrinkage and cracking after heating up to 950ºC. Geopolymers with aggregate also suffer extensive cracking due to heating although the shrinkage was less than that of geopolymers without aggregate Dilatometer results show that geopolymer pastes shrink about 2% below 300ºC and remAln dimensionally stable up to 800ºC. The coefficient of thermal expansion of geopolymers is comparable to that of Portland cement paste. The presence of aggregate was found to reduce the shrinkage of geopolymer by 50%. Quartz aggregate, however, limits the useful working temperature range of geopolymers to below 500ºC due to a sudden expansion of quartz at 574ºC. The thermal conductivity of geopolymers was measured using a hot-wire method. The results indicated that thermal conductivity of geopolymers was similar to those of Portland cement paste. As with Portland cement, the addition of quartz was found to increase the thermal conductivity. The compressive strength of Na-PSS geopolymers is significantly influenced by the hardness, apparent porosity and the atomic ratio of Si:Al. It was found that geopolymers with an atomic ratio of Si:Al = 1.5, Na:Al = 0.6 have the highest compressive strength and hardness. It was also observed that the addition of aggregate (quartz and granite) has negligible effect on the strength of geopolymers. The bond strength between geopolymer and aggregate was measured by using a tensile test. The results indicated that sandstone aggregate provides the strongest interfacial bond with geopolymer, followed by granite and quartz. The mechanical interlocking due to the rough surface of the sandstone was believed to be responsible for the relatively high interfacial bond strength.The microstructural characterisation of Na-PSS by means of SEM (scanning electron microscopy) and TEM (transmission electron microscopy) revealed that the morphology of Na-PSS consists of aluminosilicate matrix, unreacted metakaolinite, pores and microcracks. The presence of microcracks observed by SEM and TEM are categorised as secondary microcracks formed during sample preparation. Computed Tomography Imaging (CT-Scan) results for as prepared geopolymers with and without the inclusion of aggregate did not reveal any resolvable cracks. Optical microscopy observations on polished and vacuum evacuated samples also shows the formation of cracks on the surface of geopolymers. The presence of unreacted metakaolinite was confirmed by energy dispersive spectroscopy (EDS), X-ray mapping and electron diffraction. It was also found that Na-PSS geopolymers prepared with Si:Al = 2.0, Na:Al = 1.0 are more homogeneous (less unreacted metakaolinite) than Na-PSS geopolymers prepared with Si:Al = 1.5, Na:Al = 0.6. SEM and TEM observations revealed that the interfacial zone between geopolymer paste and aggregate has the same chemical composition as the rest of the geopolymer matrix. As a result of this study there is a better understanding of the composition-microstructure-property relationship of geopolymers paving the way to the production of geopolymers with improved performance in a variety of applications.